Analysis of Village Community Recycle Participation Behavior to Maintain Environmental Quality. Empirical Evidence in Waste Banks in Indonesia - SASANA, Hadi; WIJAYANTI, Diah Lutfi; NURCAHYANTO, Herbasuki; NOVITANINGTYAS, Ivo (Journal of Environmental Management and Tourism; Vol 13 No 5 (2022): JEMT, Volume XIII, Issue 5(61), Fall 2022DO - 10.14505/jemt.v13.5(61).17, 2022)
Community participation in maintaining environmental quality through waste management is very necessary. This study aims to analyze the behavior of recycling participation in the Theory of Planned Behavior (TPB) framework. The object of the research is the village community members of the Resik Apik Waste Bank, Pati Regency, Central Java Province, Indonesia. Data were analyzed using Structural Equation Modeling - Partial Least Square (SEM-PLS). The results of the analysis show that the recycling participation behavior of rural communities with relatively low levels of education is more driven by personal norms, satisfaction with the service provided, and intention to act. Therefore, it is important to encourage the understanding and knowledge of the villagers about recycling to increase their intention and behavior in recycling waste. Indirectly, social norms are significant for recycling participants through personal norms and intentions to act.